Gypsum self-leveling agent capable of shortening layered coagulation time difference
By accurately proportioning the components of gypsum self-leveling, the difference in layered condensation time is shortened, the problem of plastic cracking during the hardening process of gypsum self-leveling is solved, and the construction performance and service life of the material are improved.
Patent Information
- Application Number
- CN202411962349.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-15
AI Technical Summary
Plastic cracking is prone to occur during hardening, resulting in a decrease in surface appearance, flatness and durability, increasing construction difficulty and maintenance costs.
By precise proportional adjustment of gypsum, cement, fillers and admixtures, the layered settling time difference of gypsum self-leveling is shortened, ensuring the consistent settling speed of the bottom layer and the surface layer, thereby avoiding plastic cracking.
It effectively shortens the layered condensed time difference of gypsum self-leveling, avoids plastic cracking, improves the construction performance and service life of the material, and reduces the subsequent maintenance and repair costs.
Smart Images

Figure QLYQS_1 
Figure BDA0005217490530000031 
Figure BDA0005217490530000041
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of gypsum self-leveling, and in particular relates to a gypsum self-leveling capable of shortening the time difference of layering and setting. Background Art
[0002] As a new type of indoor floor leveling product in China, gypsum self-leveling is gradually emerging. It is a material made of desulfurized gypsum, a product of wet flue gas desulfurization in power plants, as the core substrate, and is compounded with cement, fillers and admixtures. This material has a series of remarkable excellent properties, such as good flow properties, which can flow like a liquid during construction, greatly reducing the difficulty of the leveling process and shortening the construction time; at the same time, it also has excellent dimensional stability, whether under different temperature and humidity environment changes or in long-term use, it can maintain a relatively stable size and will not easily deform or other undesirable phenomena. More importantly, gypsum self-leveling has excellent mechanical properties, its tensile strength is relatively high, and the shrinkage stress generated by shrinkage is small. Compared with traditional cement products, this is undoubtedly a huge advantage. In the application of floor leveling, cement products often cause serious problems such as hollowing and cracking in the later stage due to large shrinkage, which not only affects the aesthetics of the floor, but also poses a great threat to the service life and safety of the floor. Gypsum self-leveling, with its own characteristics, can effectively overcome these inherent shortcomings of cement products, and naturally becomes an ideal choice for indoor leveling of buildings, providing a new and more reliable solution for indoor floor treatment of modern buildings.
[0003] Although theoretically the tensile strength of gypsum self-leveling is greater than the shrinkage stress caused by shrinkage, the situation is not so ideal in actual application. In addition to the flow cracking caused by ground leakage, gypsum self-leveling with different formulations will also have plastic cracking. Most of this plastic cracking does not occur immediately in the initial stage of the material, but is mostly concentrated in the hardening stage. In this special stage, a complex condensation reaction will occur inside the gypsum, accompanied by an exothermic process. It is precisely because of the existence of this condensation exotherm that some of the existing tiny cracks or potential cracking hazards are further expanded. Once the cracks expand, it will seriously damage the various properties of the gypsum self-leveling surface layer, such as surface appearance, flatness, durability, etc. This will not only affect the normal use function of the ground, but may also trigger a series of subsequent maintenance and repair work, increasing costs and construction difficulties.
[0004] Therefore, how to avoid plastic cracking of the gypsum self-leveling layer to the greatest extent is the key to the real application of gypsum self-leveling materials. Summary of the invention
[0005] In order to solve the plastic cracking problem existing in the practical application of gypsum self-leveling in the prior art, the inventors of the present invention found in a long-term study on gypsum self-leveling materials that the fundamental cause of the above-mentioned plastic cracking problem is that the gypsum self-leveling material undergoes a special stratification phenomenon during the hardening stage.
[0006] Specifically, in the coagulation process of gypsum self-leveling, a unique coagulation sequence from bottom to top is presented. The first part to start coagulation is the bottom area. As time goes by, this coagulation phenomenon quickly expands to the middle area in just 10min to 15min. However, at this time, the surface layer within 5mm of the surface still remains uncoagulated and softened. Then, the bottom of the gypsum self-leveling enters the exothermic stage. During this exothermic stage, since the bottom coagulates first and continues to generate heat, and the surface layer is relatively thin, its water retention capacity is extremely limited. This special structural condition causes a significant inconsistency in the coagulation speed between the bottom layer near the bottom and the surface layer near the top. In addition, the inventors of the present invention have found through repeated experimental verification and theoretical derivation that the coagulation time difference between the two, that is, the layered coagulation time difference, is closely related to plastic cracking. When the layered coagulation time difference is larger, the gypsum self-leveling layer is more likely to crack, and the degree of cracking is often more serious.
[0007] Based on the discovery of the root cause of the above-mentioned plastic cracking, in order to effectively solve the problem of plastic cracking of gypsum self-leveling during the hardening process, the present invention proposes a gypsum self-leveling that can shorten the time difference of stratification and coagulation. The gypsum self-leveling achieves effective shortening of the time difference of stratification and coagulation of the gypsum self-leveling by accurately and scientifically proportioning the components such as gypsum, cement, filler and various admixtures, thereby avoiding the plastic cracking of the gypsum self-leveling layer during the hardening process to a great extent, providing a solid and reliable technical guarantee for the wide application of gypsum self-leveling materials in many fields such as building decoration, ground leveling and industrial flooring, and strongly promoting the technological progress and development of the gypsum self-leveling industry.
[0008] The present invention specifically adopts the following technical solutions:
[0009] A gypsum self-leveling with shortened stratification setting time difference, wherein the mass of cement accounts for 2% to 4.5% of the total mass of the gypsum self-leveling, and the cement is a compound of silicate cement and sulphoaluminate cement in a mass ratio of 1.5:1 to 3:1.
[0010] The inventors of the present invention found in their research on gypsum self-leveling materials that the addition of cement is the factor that has the greatest impact on the stratification and setting time difference of the gypsum self-leveling layer, and that different types of cement mixing methods also greatly affect the stratification and setting time difference; while the length of the stratification and setting time difference has little to do with the construction thickness of the gypsum self-leveling layer and the amount of water used for mixing the gypsum self-leveling.
[0011] To this end, the above-mentioned gypsum self-leveling provided by the present invention effectively shortens the difference in stratification and setting time between the bottom layer and the surface layer in the gypsum self-leveling layer to within 15min to 60min by specifically limiting the amount of cement used in the gypsum self-leveling layer and the specific type of cement. This avoids the formation of a bottom layer and a surface layer with a large difference in setting speed due to inconsistent setting speeds in the final gypsum self-leveling layer, thereby causing plastic cracking.
[0012] At the same time, the special limitation of the above cement dosage range also ensures the shrinkage limit of the gypsum self-leveling mortar in the later stage. The cement dosage should not be too high. Too high cement dosage will easily lead to a significant increase in the size change rate of the gypsum self-leveling mortar in the later stage; and the higher the cement dosage, the greater the slurry flow loss and the greater the risk of hollowing and cracking of the gypsum self-leveling mortar in the later stage.
[0013] Furthermore, the gypsum self-leveling comprises the following components based on the total mass of the gypsum self-leveling as 100%:
[0014]
[0015] Furthermore, the gypsum is β-hemihydrate gypsum powder.
[0016] Preferably, the hard filler is stone powder and / or sand, and when it is a mixture of the two, the ratio between the two is not limited.
[0017] Preferably, the water retaining agent is a cellulose-based water retaining agent and / or a cellulose ether-based water retaining agent.
[0018] Preferably, the water reducing agent is a polycarboxylic acid water reducing agent.
[0019] Preferably, the retarder is an amino acid retarder or a composite amino acid retarder.
[0020] Preferably, the defoaming agent is a polyether defoaming agent.
[0021] Of course, in the gypsum self-leveling of the present invention, the hard filler, water retaining agent, water reducing agent, retarder and defoaming agent are not limited to the above selections, and those skilled in the art can also select other equivalent components in conventional gypsum self-leveling. DETAILED DESCRIPTION
[0022] For a better understanding of the present invention, the following examples are further illustrative of the present invention and are only used to explain the content of the present invention, but not to limit the present invention. All similar embodiments listed based on the present invention should fall within the protection scope thereof.
[0023] Example 1
[0024] A gypsum self-leveling mortar comprises the following components which are mixed evenly:
[0025]
[0026] Example 2
[0027] A gypsum self-leveling mortar comprises the following components which are mixed evenly:
[0028]
[0029] Example 3
[0030] A gypsum self-leveling mortar comprises the following components which are mixed evenly:
[0031]
[0032]
[0033] In order to verify the effect of each component in the gypsum self-leveling provided by the present invention on the difference in the stratification and setting time thereof, several comparative experiments were conducted.
[0034] Comparative Example 1
[0035] This comparative example provides a gypsum self-leveling, and the similarities with Example 1 are not repeated here, and only the differences from Example 1 are described. The gypsum self-leveling provided in this comparative example is different from the gypsum self-leveling in Example 1 only in that it does not contain cement, and the dosage of the corresponding β-semihydrate desulfurized gypsum powder is 99%, and the dosage of the polycarboxylic acid water reducer is 0.35%.
[0036] Comparative Example 2
[0037] This comparative example provides a gypsum self-leveling, and the similarities with Example 1 are not repeated here, and only the differences from Example 1 are described. The gypsum self-leveling provided in this comparative example is different from the gypsum self-leveling in Example 1 only in that the addition amount of 42.5 silicate cement is 4.5%, and sulphoaluminate cement is not contained.
[0038] Comparative Example 3
[0039] This comparative example provides a gypsum self-leveling, and the similarities with Example 1 are not repeated here, and only the differences from Example 1 are described. The gypsum self-leveling provided in this comparative example is different from the gypsum self-leveling in Example 1 only in that the dosage of sulphoaluminate cement is 4.5%, and 42.5 silicate cement is not contained.
[0040] Comparative Example 4
[0041] This comparative example provides a gypsum self-leveling, and the similarities with Example 1 are not repeated here, and only the differences from Example 1 are described. The gypsum self-leveling provided in this comparative example is different from the gypsum self-leveling in Example 1 only in that the content of sulphoaluminate cement is 2%, the content of 42.5 silicate cement is 4%, and the content of β-hemihydrate desulfurized gypsum powder is reduced to 93.66% accordingly.
[0042] Comparative Example 5
[0043] This comparative example provides a gypsum self-leveling, and the similarities with Example 1 are not repeated here, and only the differences from Example 1 are described. The gypsum self-leveling provided in this comparative example is different from the gypsum self-leveling in Example 1 only in that the content of sulphoaluminate cement is 0.6%, the content of silicate cement is 0.9%, and the content of β-semihydrate desulfurized gypsum powder is increased to 98.16% accordingly.
[0044] Comparative Example 6
[0045] This comparative example provides a gypsum self-leveling, and the similarities with Example 1 are not repeated here, and only the differences from Example 1 are described. The gypsum self-leveling provided in this comparative example is different from the gypsum self-leveling in Example 1 only in that the addition amounts of sulphoaluminate cement and silicate cement are both 1%.
[0046] Comparative Example 7
[0047] This comparative example provides a gypsum self-leveling, and the similarities with Example 1 are not repeated here, and only the differences from Example 1 are described. The gypsum self-leveling provided in this comparative example is different from the gypsum self-leveling in Example 1 only in that the addition amount of sulphoaluminate cement is 0.33% and the addition amount of silicate cement is 1.67%.
[0048] The properties of the gypsum self-leveling mortars of Examples 1 to 3 and Comparative Examples 1 to 7 are shown in Table 1 below.
[0049] Table 1 Performance of gypsum self-leveling mortar of Examples 1 to 3 and Comparative Examples 1 to 7
[0050]
[0051] By comparing Example 1 with Comparative Examples 1, 2, and 3, it can be seen that when no cement is added, the stratification and condensation time of the gypsum self-leveling is short and its 30-minute flow loss is low, but the surface strength is low and there is a water seepage problem, so cement is a necessary component. At the same time, from the composition of the cement component in the formula, the full silicate cement ash will lead to a long stratification and condensation time and a large 30-minute flow loss, which is not conducive to the construction of gypsum self-leveling; if the formula is all sulfoaluminate cement, although the shrinkage and stratification condensation time are reduced, there is a problem of large 30-minute flow loss.
[0052] Comparing Example 2 with Example 3, the delamination setting time increases when the cement component dosage is reduced, but the 28d absolute shrinkage decreases, and the presence or absence of sand has no effect on the delamination setting time.
[0053] It can be seen from the comparison between Example 1 and Comparative Example 4 that if the amount of cement is excessive, although the stratification and setting time is reduced, the 30-minute flow loss is increased, the 28-day absolute drying shrinkage is also aggravated, and hollowing and cracking are likely to occur in the later stage.
[0054] It can be seen from the comparison between Example 1 and Comparative Example 5 that if the amount of cement is insufficient, the stratification and setting time will be greatly increased.
[0055] Combined with the change law of the stratified coagulation time of comparative examples 4, 4 and 5, this is because the stratified coagulation time shows a trend of increasing first and then decreasing with the increase of cement production. Although no cement or extremely low cement content helps to reduce the stratified coagulation time, it will also lead to too low surface strength, which is not desirable; and although too high cement content shortens the stratified coagulation time, it will cause an increase in 30min flow loss and 28d absolute dry shrinkage, and hollowing and cracking problems are prone to occur in the later stage. It can be seen that only the appropriate cement content in the present invention can help balance the comprehensive performance of shorter stratified coagulation time and good 30min flow loss and 28d absolute dry shrinkage.
[0056] By comparing Example 1 with Comparative Examples 6 and 7, it can be seen that for a specific compound of sulphoaluminate cement and silicate cement, the ratio between the two will also greatly affect the stratification setting time. Too low or too high a ratio will lead to an increase in the stratification setting time, which is not conducive to a good setting effect in gypsum self-leveling construction.
[0057] It should be noted that the dosage of water retaining agent, water reducing agent, retarder and defoamer in the above embodiments is only an individual example of the technical solution and is not intended to limit all of them. As conventional components of gypsum self-leveling in the field, those skilled in the art can make appropriate adjustments in addition to the specific dosages provided in the above embodiments, referring to the conventional dosages in the field, which all fall within the scope of protection of the present invention.
[0058] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A gypsum self-leveling material for shortening the time difference of layer setting, characterized in that: In the gypsum self-leveling, the mass of cement accounts for 2% to 4.5% of the total mass of the gypsum self-leveling, and the cement is a compound of silicate cement and sulphoaluminate cement in a mass ratio of 1.5:1 to 3:
1.
2. The gypsum self-leveling according to claim 1, characterized in that: The gypsum self-leveling comprises the following components based on the total mass of the gypsum self-leveling being 100%:
3. The gypsum self-leveling according to claim 1 or 2, characterized in that: The gypsum is β-hemihydrate gypsum powder.
4. The gypsum self-leveling according to claim 1 or 2, characterized in that: The water retaining agent is a cellulose water retaining agent and / or a cellulose ether water retaining agent.
5. The gypsum self-leveling according to claim 1 or 2, characterized in that: The water reducing agent is a polycarboxylic acid water reducing agent.
6. The gypsum self-leveling according to claim 1 or 2, characterized in that: The retarder is an amino acid retarder or a composite amino acid retarder.
7. The gypsum self-leveling according to claim 1 or 2, characterized in that: The defoamer is a polyether defoamer.